169 PITX2C deficiency augments the anti-arrhythmic properties of flecainide: results in a mouse model and validation in a human atrium simulation study. (6th June 2015) - Syeda, Fahima; Holmes, Andrew P; Yu, Ting Y; Tull, Samantha P; Riley, Genna; Jousset, Florian; Kucera, Jan; Rohr, Stephan; Fabritz, Larissa; Kirchhof, Paulus
Abstract : Background and objectives: Polymorphisms close to the PITX2 gene on chromosome 4q25 are associated with incident and recurrent atrial fibrillation (AF). Carriers of variant rs10033464 respond relatively well to antiarrhythmic drug therapy with sodium channel blockers. To test whether altered atrial PITX2 mRNA expression alters the electrophysiological effect of sodium channel blockers, we studied the effect of flecainide (Flec) in hearts of mice with heterozygous Pitx2c gene deletion, a model for reduced Pitx2 mRNA expression and AF susceptibility. Methods: We assessed the effect of 1µM Flec on left atrial (LA) monophasic, transmembrane and optical action potentials in Pitx2c +/– mice and their wild type (WT) littermates. We measured conduction velocity (CV), action potential duration (APD), AP amplitude (APA), maximum upstroke velocity (dV/dtmax ) and resting membrane potential (RMP) during atrial pacing at 80–120 ms fixed-rate cycle lengths (CL); and effective refractory periods (ERP) with arrhythmia inducibility during programmed (S2) stimulation. Post-repolarisation refractoriness (PRR) was defined as the difference between ERP and APD90. We assessed whether the electrophysiological changes associated with reduced Pitx2c mRNA expression alters the response to sodium current (INa ) block using the Courtemanche et al . human atrial model. Taqman low density array analysis was also used to measure changes in 20 ion channel, and related, genes of interest. Results: Flec abolished arrhythmias in Pitx2c +/– (6/18 base vs 0/15 Flec, p < 0.05) but not in WT atria (3/15 base vs 3/12 Flec). Flec doubled the increase in ERP in Pitx2c +/– atria compared with WT (Pitx2c +/– 14 ± 2 ms, n = 13 vs WT 7 ± 2 ms, n = 10; p < 0.05), and tripled post-repolarisation refractoriness (PRR; Pitx2c +/– 21 ± 3 ms, n = 6 vs WT 6 ± 4 ms, n = 6, p < 0.01). Pitx2c +/– atria had a slightly more positive resting membrane potential (WT –70 ± 0.7 mV, n = 30 cells vs PITX2c +/– –68 ± 0.7 mV, n = 32 cells, p < 0.05) and lower APA (WT 78 ± 1.2mV, n = 30; Pitx2c +/– 73 ± 1.3 mV, n = 32). Flec had no effect on the RMP but reduced CV, APA and dV/dtmax in both genotypes to a similar extent. Hearts with PRR were not susceptible to arrhythmias (0/17). As with the isolated hearts, INa block prolonged PRR in the Pitx2c deficiency simulation (500 ms CL: reference model 30ms; Pitx2c deficiency model 42 ms) and had no differential effects of INa on RMP, CV, APD, or dV/dtmax . The human atrial model thus qualitatively reproduced the experimental findings. mRNA expression of Kcnk5 and Kcna6 was altered in Pitx2c +/– left atria. Conclusion: Flecainide suppresses atrial arrhythmias in mice with reduced Pitx2 mRNA expression. We propose that this genotype-specific antiarrhythmic effect can be explained by a more positive resting membrane potential and higher post-repolarisation refractoriness. These data suggest that flecainide may be effective for rhythm control in carriers of genetic variants on chromosome 4q25.